Acute renal failure in cirrhosis of liver: a hospital based observational study - Mili, Chakradhaj; Laskar, Basanta (International Journal of Research in Medical Sciences, 2019)
Background: In general, there is a propensity among the physicians to label a patient with cirrhosis developing a raised creatinine level as HRS and treat it as such thereby ignoring the other causes particularly in this part of the country. This study was undertaken to find out the causes of acute renal failure and their outcome in cirrhotic patients. Methods: One forty three cirrhotic patients with acute renal failure were enrolled and investigated for causes of renal failure and their outcomes. Results: 92 (64.33%) patients had single factor whereas 51 (35.66%) patients had multiple factors (two or more), causing renal failure. Hypovolemia (34.27%) was the most common cause of renal failure followed by herbal medications (11.19%), HRS (11.19%) and infections (7.69%) as a single factor. Among multiple factors, 45 (31.46%) patients had hypovolemia followed by 36 (25.17%), 18 (12.58%) and 8 (5.59%) patients having infections, herbal medications and use of nephrotoxic drugs respectively. Reversibility was seen in 72 (50.35%) patients and more common in hypovolemia (85.71%) as a single factor. Total all-cause mortality was 33 (23%) and highest mortality was seen in HRS 75% (n=12) followed by infections (45.45%) and herbal medications (25%). Conclusions: Hypovolemia was the most common cause of renal failure followed by infections, herbal medications and hepatorenal syndrome. Early detection and proper volume replacement are the key points in the management. Detailed history regarding use of herbal medications is also very important issue.